Pengaruh Media Pembelajaran Peta Tematik pada Submateri Persebaran Bencana Alam di Indonesia Kelas XI IPS SMA/MA - Ardiansyah, Mursyid; Zid, Muhammad; Hotimah, Oot (UNIVERSITAS SERAMBI MEKKAH, 2025)
Based on the researcher's observations, it is known that the issue is that students feel that the teaching and learning activities lack variety because educators only use PowerPoint (PPT) as a teaching medium, even though there are many suitable teaching media for geography topics in high schools, one of which is thematic maps. The purpose of this research is to determine the influence of using thematic map learning media on students' learning outcomes. This research employs a quantitative research method with a quasi-experimental design, using pre-tests and post-tests as research instruments. The research sample was selected using purposive random sampling. The samples in this study are class XI IPS 3 and XI IPS 4 of SMAN 113 Jakarta. Data on students' learning outcomes were collected using pre-tests and post-tests. The researcher also conducted several tests, including tests for the validity and appropriateness of the learning media, tests for normality, homogeneity, and independent sample t-tests. The findings of this research show that the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. This means that there is an influence from the implementation of the thematic map learning media, and there is a difference in the average learning outcomes between the experimental group and the control group. Thematic map learning media is suitable for use as a teaching tool that can assist students in analyzing the phenomenon of the distribution of natural disasters in Indonesia. Thus, it has been proven that the use of thematic maps can lead to improved learning outcomes for students.